Necesidad de reformar el artículo 14 del código del trabajo, para tipificar y sancionar el acoso laboral - Fernández Reyes, Claudia Malibu (2014)
Work is a right universally recognized which , since the emergence of humanity , was established in a survival activity before mass production , as time has passed , it is a process through which not only goods generated and services, but also a fundamental element of the right treatment . The interest of people by increasing the production of goods and services , was to work in an activity that at certain stages of the evolution of mankind , gave priority to capital and production on the welfare of human beings generating these goods and services, Hence the incessant struggle to this day workers promoted to ensure stability and welfare . That is why practically all the nation worldwide, the right to work is recognized and protected as such , but today there are adverse factors that undermine him and threatening , as in the case of workplace bullying . Workplace bullying theme of this research , hurts job security and therefore the welfare of both the worker and the company or institution , as if co , authorities or managers of companies, General discriminatory remarks , attitudes hostile Best little or criteria or the interpretation violates the dignity and welfare of the worker, he can not properly perform their duties and therefore not only a problem in the labor circle is created , but also undermine job security and the dignity of the person.